2003
DOI: 10.1016/s0092-8674(03)00466-5
|View full text |Cite
|
Sign up to set email alerts
|

A Panoramic View of Yeast Noncoding RNA Processing

Abstract: Predictive analysis using publicly available yeast functional genomics and proteomics data suggests that many more proteins may be involved in biogenesis of ribonucleoproteins than are currently known. Using a microarray that monitors abundance and processing of noncoding RNAs, we analyzed 468 yeast strains carrying mutations in protein-coding genes, most of which have not previously been associated with RNA or RNP synthesis. Many strains mutated in uncharacterized genes displayed aberrant noncoding RNA profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
276
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 228 publications
(291 citation statements)
references
References 67 publications
14
276
0
1
Order By: Relevance
“…By contrast, these primer extension stops are both missing in alkali-treated RNA from a dus1-⌬ strain (lane g). This result confirms that Dus1p modifies U 16 tRNA Tyr has dihydrouridine residues at five positions in the D loop as well as at D 47 . We proposed above that Dus3p might be responsible for formation of D 47 , based on our quantitation of the dihydrouridine content of tRNA Tyr from a dus3-⌬ strain (Fig.…”
Section: A Primer Extension Methods For Mapping Dihydrouridine Modificsupporting
confidence: 80%
See 4 more Smart Citations
“…By contrast, these primer extension stops are both missing in alkali-treated RNA from a dus1-⌬ strain (lane g). This result confirms that Dus1p modifies U 16 tRNA Tyr has dihydrouridine residues at five positions in the D loop as well as at D 47 . We proposed above that Dus3p might be responsible for formation of D 47 , based on our quantitation of the dihydrouridine content of tRNA Tyr from a dus3-⌬ strain (Fig.…”
Section: A Primer Extension Methods For Mapping Dihydrouridine Modificsupporting
confidence: 80%
“…This suggests that Dus4p activity accounts for formation of two of the six dihydrouridine residues in tRNA Tyr . These sites could be D 20 Microarray Analysis Largely Confirms the Preliminary Model of Dus Protein Specificity-It was previously observed that the absence of dihydrouridine in tRNAs from a dus1 mutant strain could be detected by microarray, using a protocol in which the fluors are coupled directly to the cellular RNA and hybridized to an array of oligonucleotides (16). It was noted that only oligonucleotides covering tRNA positions 16 and 17 reported significant preferential hybridization to RNA from a dus1 mutant relative to RNA from a wild type strain (positive ratios), and it was concluded that the loss of dihydrouridine modification in the dus1 mutant results in higher binding affinity.…”
Section: Analysis Of Purified Trnas From Dus Mutant Strains Yields a mentioning
confidence: 78%
See 3 more Smart Citations